Agriculture and Economic Structure in the Maurya Era – An Analysis : मौर्य युग में कृषि और अर्थव्यवस्था का स्वरूप - विश्लेषण - Kumar, Yogendra (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The Maurya Empire was a significant historical power in South Asia, founded by Chandragupta Maurya. During the Mauryan period, the king was considered the head of state and exercised control through the Mauryan army. Agriculture was the backbone of the economy, although trade was gaining increasing importance. The Maurya Empire promoted Aryan civilization across most parts of India. The integration of Aryan civilization into these regions contributed to their economic development. The state maintained control over most economic activities. Taxes levied on farmers ranged from one-fourth to one-sixth of their agricultural produce. Irrigation facilities were primarily provided through embankments, and a water tax was imposed. Goods brought from cities were subjected to tolls at the gates. Several strategic measures were taken to promote economic development and strengthen the economy during this period. As a result, foreign trade also became prevalent. Abstract in Hindi Language: मौर्य साम्राज्य दक्षिण एशिया में एक व्यापक ऐतिहासिक शक्ति थी जिसकी स्थापना चंद्रगुप्त मौर्य ने की थी। मौर्य काल में, राजा को राज्य का मुखिया माना जाता था और इसे मौर्य साम्राज्य की सेना द्वारा नियंत्रित किया जाता था। मौर्यों के दौरान कृषि अर्थव्यवस्था की रीढ़ थी, हालाँकि, व्यापार लगातार महत्वपूर्ण होता जा रहा था। भारत के अधिकांश हिस्सों में, मौर्य साम्राज्य ने आर्य सभ्यता का प्रचार किया। आर्य सभ्यता में उनके समावेश के परिणामस्वरूप, इसने क्षेत्रों के आर्थिक विकास में सहायता की। अधिकांश आर्थिक गतिविधियों पर राज्य का नियंत्रण था। किसानों से वसूला जाने वाला कर उपज का 1ध्4 से 1ध्6 भाग तक होता था। सिंचाई की सुविधाएँ मुख्य रूप से सेतुबंध द्वारा प्रदान की जाती थीं और उनसे जल कर वसूला जाता था। शहरों से लाए जाने वाले सामान पर द्वारों पर टोल लगाया जाता था। उस काल में अर्थव्यवस्था को बढ़ावा देने के लिए आर्थिक विकास हेतु विशेष कदम उठाए गए। परिणामस्वरूप विदेशों के साथ व्यापार का प्रचलन हुआ। Keywords: भारत, मौर्य साम्राज्य, अर्थव्यवस्था, चंद्रगुप्त मौर्य, कृषि और उद्योग।